Das experiências de ensino-aprendizagem gestadas e geridas no Jornal da Universidade : subsídios para um projeto - Falcetta, Antônio Paim (Universidade do Vale do Rio dos Sinos, 2018)
This study proposes the identification of the training actions developed in the production relations between professionals and academics in the writing of the Jornal da Universidade (JU), monthly publication of the Secretaria de Comunicação Social of the Universidade Federal do Rio Grande do Sul (UFRGS). Through the qualitative research, the semi-structured interview was used as an instrument, to ascertain from the interviewees' narratives what they consider as formative actions and the reflections about the work dynamics in the JU that they entered into. Three were the intentions of the work: (a) to map the interpersonal and collective exchanges that improve the technical quality of the group, more specifically of the students; (b) produce content about the work processes; and (c) to assess the conditions of the human environment and its dynamics, in order to verify if (and how) they collaborate for the unfolding of actions and the learning exercises, about which success has been achieved. With the results, a proposal for a training project for the JU team was elaborated. In theoretical terms, as a pedagogical basis we come to the postulates of Paulo Freire, Moacir Gadotti and Carlos Alberto Torres, in their publications on “Pedagogia da Libertação”. In convergence with these, as a methodological substrate to the project resulting from this work, we propose principles developed in the theory of Learning Communities, especially the chapter on dialogic learning, elaborated by the Special Center for Research in Theories and Practices Overcoming Inequalities of the University of Barcelona, published in Brazil since 2003. On journalism, we have used Gramsci's ideas on "Jornalismo Integral" and Adelmo Genro Filho on the theory of journalism as a form of knowledge, respectively in "Os Intelectuais e a Organização da Cultura" and "O Segredo da Pirâmide". Concerning public communication, we find the democratic concerns that interest us in Maria Helena Weber, in the recent publication "Comunicação Pública e Política". Finally, on the question of democratic management, we refer to Naura Syria Carapeto Ferreira, in the book "Gestão da Educação: impasses, perspectivas e compromissos". For the JU team, it is a consensus that learning processes extend beyond formal environments, with multiple possibilities for learning environments.
Keywords: Pedagogia da libertação; Jornalismo integral; Gestão; Gestão democrática; Comunicação pública; Estágio; Comunidades de aprendizagem; Pedagogy of liberation; Integral journalism; Management; Democratic management; Public communication; Internship; Learning communities; ACCNPQ::Ciências Humanas::Educação